Habitat and Weather Effects on Northern Bobwhite Brood Movements - J. Scott Taylor; Kevin E. Church; Donald H. Rusch (National Quail Symposium Proceedings, 2017)
We observed radio-marked northern bobwhite (Colinus virginianus) broods (adults with chicks :S21 days old; n = 12) in Kansas during 1991-94 to test effects of weather (temperature and precipitation) and macrohabitat (composition, relative diversity, and mean distance to grassland) variables on brood home range size and daily movements at large (28.5 km2), intermediate (3.14 km2), and small (about 0.14 km2) spatial scales surrounding habitats available for broods. Principal component analyses followed by stepwise multiple linear regression indicated neither weather nor habitat influenced (P 2: 0.1) home range size at the large and intermediate scales. However, the principal component representing mean distance to grassland and percent cropland within the home range (i.e., at a small scale) was positively related to home range size. Neither temperature nor habitat influenced daily distance of movements. We concluded that brood mobility was independent of landscape-scale features, but that habitat management at smaller spatial scales could influence movements. To create optimal habitat for bobwhite, managers should consider relationships among habitat attributes and the movement of individuals, including the spatial scales at which these relationships are most important.